Integrating CRM, Biological Defense, and STEM Education to Strengthen Indonesia's Defense Human Resources - F. Sukma Wahyudin; Mia Kusmiati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Purpose –This article aims to integrate three strategic pillars in strengthening Indonesia's defense human resources (HR), namely Crew Resource Management (CRM) in military medicine, national biological defense, and STEM-based education. Design/methodology/approach –The research used a systematic literature review approach by examining literature from international databases (Elsevier, Springer, Wiley, Taylor & Francis, ACM, IEEE, ScienceDirect, SAGE, DOAJ, JSTOR) and reputable national journals (SINTA, GARUDA, BRIN). The analysis was conducted thematically with normative, empirical, and conceptual approaches. Findings –The study results show that: (1) CRM effectively improves communication, coordination, and decision-making of military medical teams in crisis situations; (2) the establishment of a Biological Defense Agency is urgently needed to address the threat of pandemics, bioterrorism, and transnational biosecurity; and (3) STEM education has been proven to strengthen innovation, adaptability, and the competence of the younger generation of defense personnel. The integration of these three aspects results in the CRM–Bio-Defense–STEM Nexus conceptual framework as the foundation for developing Indonesian defense human resources towards the 2045 vision. Practical implications –This study recommends strengthening national policies through: (1) a STEM-based defense curriculum, (2) CRM training in military medical education and operations, and (3) the establishment of a special biological defense institution as the front line in facing biological threats.Originality/value –This article provides a new contribution in the form of an integrative conceptual model of CRM–Bio-Defense–STEM that has never been studied holistically in the context of Indonesian defense, while also offering a strategic framework for the development of adaptive, innovative, and resilient national defense human resources.